Strategi Pemasaran Pembiayaan Produk BSI Oto Dalam Menarik Minat Masyarakat Kota Jambi Pada Bank Syariah Indonesia (KCP Jambi Sipin Bakaruddin) - Mila Sukmawati; Rafiqi Rafiqi; Ary Dean Amri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the marketing strategy of BSI Oto financing products in attracting public interest in Jambi City at Bank Syariah Indonesia KCP Jambi Sipin Bakaruddin. The research employed a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The results indicate that the implemented marketing strategy encompasses the application of the marketing mix (7P), namely quality products based on murabahah contracts, competitive pricing, strategic branch locations, promotion through cooperation with dealers and digital media, professional services, transparent financing processes, and representative physical evidence of facilities. The main obstacles encountered are the low level of public understanding of sharia-based financing and intense competition with conventional financing institutions. The proposed alternative strategies include intensifying public education, optimizing digital promotion, and strengthening partnerships with vehicle dealers. This research is expected to serve as a reference for the development of sharia financing marketing strategies.